PREPARAÇÃO DE BIOCOMPÓSITO À BASE DE AMIDO TERMOPLÁSTICO REFORÇADO COM FIBRAS DE EUCALIPTO: AVALIAÇÃO DO EFEITO DO TAMANHO DAS FIBRAS NAS PROPRIEDADES MECÂNICAS E DE SORÇÃO - Luisa B. dos Santos; Tonny A. Moreira; Cleocir J. Dalmaschio; Marta A. Machado (Química Nova)
This study investigated the preparation of a thermoplastic starch-based (ATP) biocomposite reinforced with eucalyptus fibers (FE), focusing on how fiber size affects the properties. The natural fibers were chemically processed using alkaline and bleaching treatments of eucalyptus bark. Subsequently, they were characterized by infrared spectroscopy (FTIR) and X-ray diffraction (XRD) to evaluate alterations in fiber composition and crystalline structure. Samples of biocomposites were prepared with a fixed fiber content (20 wt.%) and variations in particle size (dp): ATP/FE600 (600 μm ≤ dp < 1180 μm), ATP/FE250 (250 μm ≤ dp < 600 μm), and ATP/FE75 (75 μm ≤ dp < 250 μm). The samples were characterized by optical and scanning electron microscopy, mechanical tests, moisture absorption, and swelling analysis. Results indicated significant effects of fiber size on the biocomposite properties. Notably, the larger fibers present in ATP/FE600 exhibited superior tensile strength and elastic modulus, while this sample demonstrated reduced moisture absorption and swelling tendencies. Microscopic images revealed enhanced matrix-fiber adhesion in ATP/FE600, highlighting the importance of proper fiber size. The optimization of fiber size emerges as a relevant strategy for improving the mechanical attributes and mitigating moisture/water absorption tendencies in starch-based thermoplastic biocomposites, contributing to sustainable and high-performance materials.